How animal models can be utilized to find new biomarkers for cardiovascular diseases. Issue 6 (29th March 2023) - Shimosawa, Tatsuo
Abstract: It has been more than 60 years since the colonized genetic model of hypertension was first established. Model animals contribute greatly to the advance of understanding of the pathophysiology and development of effective therapy. In this review, the author focuses on two points: gene-related biomarkers and the use of humanized mice to search for biomarkers. First, the author provides an overview of the history of the establishment of hypertension and salt-sensitivity model rats, as well as advances in genetic analysis of causative genes of hypertension and the theory of renal causes of salt-sensitive hypertension. The recent animal model analysis adds the notion of the importance of epigenetic alterations in addition to the genetic causes of hypertension. Both germline mutations and epigenetic analysis of congenic animal models are complementary and should carry out furtherly. Among epigenetic factors, non-coding RNA is a promising new 'liquid biopsy' which is originally applied to diagnose cancers by detecting cancer cell-derived DNA, RNA, or other molecules in a person's body fluid and now it can be applied to any pathophysiological conditions. Then, the author reviews the usefulness of humanized mice. Few studies have used such mice in cardiovascular research, but the present study highlights a study of immune-related disease and the search for biomarkers in such mice. Perspectives on using humanized mice in cardiovascular research are discussed.